Influência da adição de fibras curtas de aço e de nylon no comportamento e na resistência ao esforço cortante de vigas de concreto armado - Carla Maria Montanari Goncalves (2003)
The results of an experimental investigation of the effects of short fibers on the shear behavior and strength of simply supported reinforced concrete beams are presented. Steel (Xorex) and nylon (Du Pont) fibers, with different shapes as well as lengths and crosssections, were used in the beams. Midspan deflections and strains on the concrete and on the longitudinal and transversal reinforcement were measured during the tests. A comparative analysis with respect to the results obtained by VIDAL FILHO, in which similar beams without and with Dramix Steel fibers were tested, is also presented. The test results indicate expressively the better performance of the beams made with steelfibers. These beams exhibited smaller crack width and spacing and consequently more stiffness and load carrying capacity. The results also show that the steel fibers improve the shear resisting mechanisms of the concrete represented by the aggregate interlocking and dowel action and behave as an additional transverse reinforcement, consequentlyreducing the stresses in the stirrups. In this study, the steel fibers employed had a better performance than the nylon ones.